2009
DOI: 10.1093/alcalc/agp070
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Dehydrogenase as a Marker of Alcohol Dependence

Abstract: GLDH is an equally accurate marker of alcoholism in comparison to others, if its significantly faster decrease is taken into consideration. We strongly believe that watching changes in the activity of laboratory markers of alcoholism is an effective yet overlooked aid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…GLDH converts glutamate to α-ketoglutarate releasing ammonia and vice versa, whereas GS condenses glutamate and ammonia to glutamine. Although GLDH has been suggested to be a potential alcohol dependence biomarker, 44 we found that GS activity could be an underlying mechanism for positive acamprosate treatment outcome as glutamine was negatively correlated with both glutamate and ammonia in the responder group. It is important to note that acamprosate is most effective in maintaining abstinence when patients were detoxified before initiating acamprosate treatment.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…GLDH converts glutamate to α-ketoglutarate releasing ammonia and vice versa, whereas GS condenses glutamate and ammonia to glutamine. Although GLDH has been suggested to be a potential alcohol dependence biomarker, 44 we found that GS activity could be an underlying mechanism for positive acamprosate treatment outcome as glutamine was negatively correlated with both glutamate and ammonia in the responder group. It is important to note that acamprosate is most effective in maintaining abstinence when patients were detoxified before initiating acamprosate treatment.…”
Section: Discussionmentioning
confidence: 61%
“…It is also important to consider that ammonia can cross the blood–brain barrier and has been shown to result in increased glutamate levels in the brain. 43 As glutamate dehydrogenase (GLDH) and GS have an important role in signaling regulation in alcohol dependence, 44 we also analyzed their metabolic products. GLDH converts glutamate to α-ketoglutarate releasing ammonia and vice versa, whereas GS condenses glutamate and ammonia to glutamine.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate dehydrogenase (GLDH) has been used as a marker of liver function as well as a marker for recent alcohol consumption in alcoholics (Kravos and Malesic, 2010). This reaction proceeds towards the direction of oxidative deamination of glutamate, which releases ammonia, normally with an activity of 6.4 U/L for women and 11.0 U/L for men.…”
Section: The Digestive Systemmentioning
confidence: 99%
“…Using proteomic technologies, elevated levels of IgA, α1-antichymotrypsin, haptoglobins, apoprotein A-I, or decreased apoprotein A-II and fibrinogen αE chain, were identified [48]. The increase in glutamate dehydrogenase and urinary alanine aminopeptidase, the decrease in erythrocyte aldehyde dehydrogenase, or increase in serum hyaluronate, were also suggested as a glycoconjugate-related markers of alcohol-dependence and alcohol-induced tissue damage [15,40,49]. However, all the aforementioned markers need further confirmatory research.…”
Section: Other Markersmentioning
confidence: 99%